TINDAK TUTUR ILOKUSI TOKOH WANITA DALAM NOVEL LA FIANCÉE ÉTAIT À DOS D’ÂNE - Icha Priliskha Yunisty; Yuliarti Mutiarsih (BAHAS, 2020)
AbstractThis research aims to explain the act of illocutionarry in the novel entitled La Fiancée Était À Dos d’Âne by Vénus Khoury-Ghata. The research questions discussed in this research are thow to characterize the female characters in that novel, then what type of act of illocutionarry found in female speech in that novel. The method used in this research is descriptive-qualitative, by analyzing data contained in the dialogues. The results explain that there are nine females characters which Yudah as a main character has a representation of a strong, friendly, patient, and innocent, and the others as the supporting characters. The data shows that as many as 25. The data shows that as much as 51% for representative speech acts with the speech function as explaining, contradicting, thinking, informing, confessing, defending, criticizing, and expressing. 41% for directive speech acts with speech functions as asking, asking, inviting, obliging, advising, ordering, prohibiting. Commissive speech acts cover 4% with the speech function as promising and offering. Expressive with a speech function of hope and declarative with a speech function of baptizing has respectively 2%. Keynote: illocutionarry speech act, female character, novel AbstrakPenelitian ini bertujuan untuk menjelaskan tindak tutur ilokusi pada novel La Fiancée Était À Dos d’Âne karya Vénus Khoury-Ghata. Tujuan dari penelitian ini adalah untuk mengetahui karakter tokoh wanita di dalam novel, dan jenis tindak tutur ilokusi apa yang ditemukan dalam tuturan tokoh wanita pada novel tersebut. Hasil penelitian menjelaskan bahwa terdapat 9 tokoh wanita, Yudah sebagai tokoh utama mempresentasikan seorang gadis yang tangguh, ramah, sabar, dan lugu. Kemudian data menunjukkan bahwa sebanyak 51% untuk tindak tutur representatif dengan fungsi tuturan sebagai menjelasan, pertentangan, berpikir, menginformasikan, mengaku, mempertahankan, mengkritik, dan mengutarakan. 41% untuk tindak tutur direktif dengan fungsi tuturan sebagai menanyakan, meminta, mengajak, mewajibkan, menasehati, menyuruh, melarang. Tindak tutur komisif mencakup 4% dengan fungsi tutur sebagai menjanjikan, dan menawarkan. Ekspresif dengan fungsi tutur harapan maupun deklaratif dengan fungsi tutur membaptis masing-masing sebanyak 2%.Kata kunci: ilokusi, tokoh wanita, novel.